Toksisitas Hematologi Regimen TAC (Docetaxel-Doksorubisin-Siklofosfamid) dan FAC (Fluorourasil-Doksorubisin-Siklofosfamid) pada Pasien Kanker Payudara di Rumah Sakit Kanker Dharmais Jakarta: Analisis Data Rekam Medik 2007-2008 - RETNOSARI ANDRAJATI; RIZKA ANDALUSIA (Indonesian Journal of Cancer)
Breast cancer in Indonesia the second most common cancer in women after cervical cancer in 2008. FAC and TAC are chemotherapy regiments for breast cancer that give good therapy response but affect patient haematology. Study about hematologic toxicity of TAC and FAC in breast cancer patient has not been conducted in Dharmais Cancer Hospital. The purpose of this study was to determine hematologic toxicity of 6 cycles TAC (docetaxel 75 mg/m2, doxorubicin 50 mg/m2 and cyclophosphamide 500 mg/m2, day 1, 21) and FAC (fluorouracil 500 mg/m2, doxorubicin 50 mg/m2 and cyclophosphamide 500 mg/m2, day 1, 21) in breast cancer patients in Dharmais Cancer Hospital.